Conservation and use of genetic resources (Genebanks) - Selvarajan, R.; Uma, S.; Ravi, I.; Mayilvaganan, M.; Thanagvelu, R.; Karpagam, C.; Chase, Rachel; Ruas, Max; Carpentier, Sebastien; Roux, Nicolas (2024)
The document is the final technical report for the project titled "Conservation and Use of Genetic Resources (Genebanks)," conducted by the ICAR-National Research Centre for Banana (ICAR-NRCB). The report outlines the successful hosting of an international workshop on "Phenotyping for Drought Tolerance" in March 2023, with international participants from various countries. The workshop aimed to train researchers on identifying drought-tolerant crop genotypes under field conditions, with a focus on banana cultivation. The event featured lectures, practical sessions, and field visits.